FAKTOR DAYA TARIK DAN KINERJA PELAYANAN MENURUT PERSEPSI MAHASISWA : STUDI FE UNNES - Ismiyati, Ismiyati (Dinamika Pendidikan, 2011)
The objective of the research was to find the factors of the Economic Faculty s magnetism for Students Candidates to continue studying at the Economics Faculty, Semarang State University. Then, this study assessed the performances of those factors after they became Economics students. The sample of the study were Economics Faculty students from three departments; Accounting, Management, and Development Economics which consisted of 64 students on different semesters as th respondents. The data were analyzed by factor analysis to find the factors which became the Economics Facultys magnetism. Then, the data were analyzed by Wilcoxon Rank Test to test the performances of those factors with the level of certainty was 95%. The result of the study showed that there were 4 main factors which became Economics Faculty magnetism, they are; 1) Superiority, 2) Promotion, 3) Location and 4) Performance. Furthermore, the respondents stated that the performance of superiority factor was not satisfying while the performances of promotion, location and per formance factors were satis fying.